COVID-19 and Its Impact on African Trade - Glauber, Joseph W. (2020)
Joseph Glauber POLICY SEMINAR Virtual Event - COVID-19, global markets and African agricultural trade: Impacts on growth and food security Organized by IFPRI, with support from the United States Agency for International Development (USAID) SEP 17, 2020 - 09:30 AM TO 11:00 AM EDT